PENGARUH JENIS DAN LEVEL TEPUNG CANGKANG KERANG SIMPING DAN KERANG HIJAU DALAM PAKAN TERHADAP PERFORMA PRODUKSI TELUR AYAM LOHMAN - Nonok Supartini; Erik Priyo Santoso; Salma Bahrun; Mohamad Nurul (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to determine the effect of the level and type of shellfish flour in feed formulations to increase egg production and quality. The method used was a nested complete randomized design consisting of 3 treatments and three replications, each replication using three chickens. The treatment used was several sources of calcium in the basal diet, namely without a calcium source 0%, green clamshell flour 1% 2% 3%, and scallop shell flour 1% 2% 3%. The variables observed were feed consumption, FCR, HDP, hen mash, whole egg index, white egg index, egg yolk index, egg yolk weight, eggshell thickness, and eggshell weight. The results showed that the treatment gave a very significant difference (P0.01) in feed consumption, and significantly different (P0.05) on the egg yolk index and eggshell weight and did not provide a significant difference (P0.05). on FCR, HDP, and hen mash.